Organizational Culture in Cultural Organizations in East Java - Rofiq, Arif (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: To study and analyze cultural values, interaction, communication, and factors that influence the formation of a strong organizational culture in dance studios in East Java. The objectives of this study also include providing a better understanding of the cultural dynamics of dance studios, contributing to the development of policies and management strategies for cultural organizations, as well as providing input and recommendations to the government, communities, and cultural actors in East Java. Design: This research uses a qualitative approach by involving data collection through interviews, observations, and documentation studies. The collected data is analyzed in depth with a qualitative approach, through data coding, pattern identification, key findings, and emerging themes. The validity and reliability of the study are guaranteed through data triangulation, peer examination, and discussion with cultural experts or related experts. Findings: The results of this study reveal various cultural values embraced by dance studios in East Java, such as gotong royong, local wisdom, the spirit of collaboration, and respect for traditions and customs. These values become a strong foundation for carrying out cultural activities and provide a strong identity for dance studios in East Java. The study also observed that interactions between dance studio members in East Java were characterized by mutual respect, support, and cooperation. Effective and open communication is an important factor in maintaining harmony and smooth cooperation in the dance studio. The success of dance studios in East Java in carrying out cultural tasks and functions depends heavily on the ability of members to interact, communicate, and work together synergistically. In addition, this study identifies several factors that influence the formation of a strong organizational culture, such as inspiring leadership, organizational commitment to culture, recognition of individual contributions, and culture-oriented human resource development practices. These factors play a role in creating an organizational environment that nurtures and encourages a positive and strong culture. Practical implications: This research is expected to provide a deep understanding of organizational culture in dance studios in East Java, as well as contribute to the development of policies and management practices of cultural organizations in the region. The research results will be presented in a structured research report and disseminated to the government, society, cultural actors, and other related parties. Paper type: Research paper